Proyecto integrador desde las artes plásticas: una experiencia creativa en el aula - Rodríguez Ochoa, Dilsa Yamile; Aragón Bueno, María Gracia; Grande Núñez, Carlos Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present text tries to relate the pedagogical processes from the plastic Arts Education in dialogue with the didactic transversal strategies within the curriculum in the training of teachers of the Degree in Basic Education with emphasis in Math- ematics, Humanities, and Spanish Language. Besides the document addresses the importance of arts education within the curriculum at this level of educational training, as a fundamental transversal area based on guidelines from the General Education Law (115 of 1994). Likewise, significant pedagogical experiences based on the implementation of plastic arts in real contexts are addressed, attending to strategic needs within the classroom in a creative way in one of the Regional Dis- tance Education Centers (Cread).